PERAMALAN VOLUME PENJUALAN TABUNG APAR (ALAT PEMADAM API RINGAN ) DENGAN MENGGUNAKAN METODE MONTE CARLO (Studi Kasus : PT Sanindo Perkasa Abadi) - Abror, Akhdan; Nurul Hamidah, Mas; Alim, Syariful (Fakultas Teknik dan Teknologi - TANRI ABENG UNIVERSITY, 2024)
Forecasting is the art and science of predicting future events. In this research the author uses sales volume forecasting using the Monte Carlo method. This case study is at one PT Sanindo Perkasa Abadi. The problem that is often experienced by PT Sanindo Perkasa Abadi is the excess and shortage or supply of APAR tubes (light fire extinguishers) at certain times which causes reduced income. With these problems, careful planning is needed to be able to estimate the inventory of goods so that it does not result in reduced income for the Company. The method used is Monte Carlo simulation. This method uses a probabilistic approach so that it is able to consider uncertainty. Demand forecasting is carried out for twelve months and uses historical data on actual demand in 2019 and 2022. The calculation results are that for the prediction of the AF11E 3kg fire extinguisher in 2021, the accuracy is 28.67% and the MAE error value = 19.692, the prediction for the AF11E 6kg fire extinguisher in 2020 is accurate. 40.75% and the MAE error value = 10,583, for the prediction year for the 6kg AF11E fire extinguisher in 2021, the accuracy was 47.50% and the MAE error value = 3,833, for the prediction year for the AF31 3kg fire extinguisher in 2020, the accuracy was 48.67% and the MAE error value = 4,750, for the prediction year for the AF31 6kg fire extinguisher in 2019, the accuracy was 47.75% and the MAE error value = 5,583, and for the prediction year for the AF31 6kg fire extinguisher in 2021, the accuracy was 46.83% and the MAE error value = 7,750.